Analisa Perancangan Tata Letak Fasilitas Gudang dengan Metode Class Based Storage (Studi Kasus: PT Emitraco Transportasi Mandiri) - Rachmannda, Ibnu Ichwan; Hariastuti, Ni Luh Putu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT Emitraco Transportasi Mandiri is a company engaged in Trucking, Stuffing, Container Depot, and Warehousing. Therefore, it is closely related to the design of the facility layout. A poorly designed warehouse layout will disrupt the performance of the storage system. This study was conducted to increase the effectiveness and efficiency in warehouse design. Class Based Storage is used to sort goods that are often out or sold with the ABC classification, then propose a layout that is in accordance with the classification. The results of the analysis and evaluation show that the initial layout has a material movement of 22568 m2 and the proposed layout is 22349 m2, this result provides a difference of 219 m2 which has an impact on the level of efficiency and effectiveness of goods movement in the warehouse by 0.97%. the company needs to change the placement of goods in order to reduce the distance.